The relationship between historical development and potentially toxic element concentrations in urban soils. (January 2017) - McIlwaine, Rebekka; Doherty, Rory; Cox, Siobhan F.; Cave, Mark
Abstract: Increasing urbanisation has a direct impact on soil quality, resulting in elevated concentrations of potentially toxic elements (PTEs) in soils. This research aims to assess if soil PTE concentrations can be used as an 'urbanisation tracer' by investigating geogenic and anthropogenic source contributions and controls, and considering PTE enrichment across historical urban development zones. The UK cities of Belfast and Sheffield are chosen as study areas, where available shallow and deep concentrations of PTEs in soil are compared to identify geogenic and anthropogenic contributions to PTEs. Cluster analysis and principal component analysis are used to elucidate the main controls over PTE concentrations. Pollution indices indicate that different periods of historical development are linked to enrichment of different PTEs. Urban subdomains are identified and background values calculated using various methodologies and compared to generic site assessment criteria. Exceedances for a number of the PTEs considered suggest a potential human health risk could be posed across subdomains of both Belfast and Sheffield. This research suggests that airborne diffuse contamination from often historical sources such as traffic, domestic combustion and industrial processes contribute greatly to soil contamination within urban environments. The relationship between historical development and differing PTEs is a novel finding, suggesting that PTEs have the potential for use as 'urbanisation tracers'. The investigative methodology employed has potential applications for decision makers, urban planners, regulators and developers of urban areas. Highlights: The concentrations of various potentially toxic elements are investigated in Belfast and Sheffield soils. Both geogenic and anthropogenic sources of the elements are identified. The historical development of both cities is compared with element enrichment in soil. Background values are calculated for the anthropogenic elements. Links between historical city development and element concentrations are identified. Abstract : Potentially toxic elements have the potential for use as 'urbanisation tracers' due to their association with different historical anthropogenic sources.